IMPROVING THE ABILITY TO UNDERSTAND MATHEMATICS LEARNING FOR MI THROUGH DISCOVERY LEARNING MODEL FOR PGMI STUDENTS - Ridania Ekawat; Yunardi` (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The problem in this research was that PGMI students at UMSB found it difficult to understand mathematics learning for MI. It was observed that the students did not participate actively and did not think creatively. This was indicated by low participation in learning activities. The objective of this research was to improve the ability to understand mathematics learning at PGMI through the Discovery Learning model. This research employed qualitative and quantitative methods with the type of Classroom Action Research. The research was conducted in two cycles, with two meetings in each cycle. Data were collected through pretest, posttest, observations, and interviews related to the learning process before and after the implementation of the Discovery Learning model. The pretest results showed that 45% of students thought quite creatively, 50% thought less creatively, and only 5% thought very creatively. The first meeting in Cycle I was conducted through an online Discovery Learning model using the Zoom application. The results indicated that 12.5% of students had a very high level of activeness, 25% had a high level of activeness, and 62.5% had a moderate level of activeness. The percentage of students who thought creatively was 67%, those who thought less creatively were 25%, and 8% thought very creatively. In Cycle II, the level of students’ activeness increased, with 17% of students showing very high activeness, 67% showing high activeness, and 16% showing moderate activeness. It was also found that 80% of students thought creatively and 20% thought very creatively. The increase in the average score and the average percentage of completeness indicated that the implementation of the Discovery Learning model improved PGMI students’ understanding of mathematics learning for MI.